Natural factors influencing whitefly attack in sweet pepper - Leite, Germano Leão Demolin; Picanço, Marcelo; Jham, Gulab Newandram; Gusmão, Marcos Rafael (Pesquisa Agropecuaria Brasileira, 2002)
The objective of this work was to determine the effect of rainfall, temperature, relative humidity, predators, parasitoids, plant age, leaf chemical composition (GC/MS-gas chromatographic-mass spectrometric analysis of hexane extract) and levels of N and K on the intensity of attack by Bemisia tabaci biotype B (Genn.) (Homoptera: Aleyrodidae) on sweet pepper (Capsicum annuum) var. Myr-10. Out of the four peaks detected in the hexane extract on GC/MS analysis, areas of the peak eluting at 28.178 and 42.755 min correlated positively to the nymph and adult population, respectively. The peak eluting at 36.352 min correlated negatively with the nymph population.